The contribution of leaders' and managers' attributes, values, principles, and behaviours to the sustainable implementation of Lean in healthcare: A realist review protocol [version 1; peer review: 2 approved] - Seán Paul Teeling; Anne Marie Keown; Martin McNamara (HRB Open Research)
Background Global healthcare faces challenges such as rising costs, budget constraints, aging populations, chronic diseases, and increasing patient expectations. Healthcare organisations are deploying continuous improvement methodologies to address these challenges. Lean, derived from the Toyota Production System, focuses on eliminating non-value-adding activity and enhancing efficiency, making it a prominent quality improvement approach in healthcare. Effective implementation of Lean requires robust leadership to sustain improvements and foster a culture of continuous improvement. However, the attributes, values, principles, and behaviours of effective Lean leaders in healthcare remain underexplored. Methods This realist review protocol details methods to research how leaders' and managers' attributes, values, principles, and behaviours contribute to the sustainable implementation of Lean in healthcare. Following the RAMESES guidelines, a five-stage structured methodology will be used: defining the scope of the review and developing initial theories, developing the search strategy, reviewing primary studies and extracting data, synthesising evidence and developing conclusions, refining theory iteratively, and disseminating findings. An Expert Panel and reference groups of healthcare managers and leaders will refine candidate programme theories (CPTs) into initial programme theories (IPTs), guiding detailed evidence searches and data extraction. Conclusion This realist review will deepen our understanding of the specific mechanisms by which leadership impacts Lean implementation outcomes in the context of acute hospitals. By exploring how leadership attributes, values, principles and behaviours shape outcomes for diverse stakeholders, the review aims to provide critical insights into the dynamics driving the success of Lean in healthcare. The findings will inform policy and practice, enhancing leadership strategies to improve patient and staff experiences, patient outcomes, and organizational performance.